(untitled) (Journal of Tikapur Multiple Campus, 2024)
Population aging is taking place rapidly in Nepal. The purpose of this article is to present the aging situation in Nepal. Data from different published sources are used in this article. There are 29.1 million older people in Nepal as of the 2021 census. The proportion of older people 60 years and older reached 10.12 percent of the total population. The older population growth rate is 3.29%. The proportion of older people increased by 38% in the last decade. Mountain and Hill have a higher proportion of older people while Terai has a slightly low. The proportion of older people living in rural areas is higher than in urban areas. Gandaki, Koshi, and Bagmati provinces have a higher proportion of older people compared to the national average. On the other hand, Madhesh, Lumbini, Sudurpashchim and Karnali provinces have a lower proportion of older people. Understanding these geographical variations through the National level study is necessary. Such a study can aid in formulating targeted policies and services to cater to the specific needs of older populations in each area. By taking proper actions through policies, Nepal can ensure that its aging population continues to live healthy, productive, and fulfilling lives.